A Critical analysis of Arabic verses in Tarikh-e Beihaqi - M.R Najjarian; M Iranmanesh (متن شناسی ادب فارسی, 2009)
Tarikh-e-Beihaqi is a prose masterpiece of the 5th century A.H. and a model of compiling history for the successors. It is also an example of exquisite prose and a treasury of literary examples along with some indications of social and political conditions of those days. Beihaqi had mastered Arabic diction and literature as the requisite of the secretarial offices then. As the prose of Tarikh-e-Beihaqi is of the mutual nature and different from the prose of the first period, there are not so many Arabic verses. In these verses, Beihaqi mentions the name of each poet before or after the poem. Some verses are related to a historical event which Beihaqi uses to confirm his claims not necessarily related to the history and some of them are merely of advisory and counseling nature. The composers of the poems living in different periods including pre-Islamic and Islamic periods such as the beginning of Islam, Umavids and Abbasids âpoets like Motanabbi and Abu-l-Ataheye and so on are chosen by him. However, some composers are not yet known for instance a single verse belonging to Imam Ali is not attributed to him. Also the attribution of some poems seems to be incorrect and some errors could be noted in the text. It seems that Beihaqi has changed some verses of his own however, these manipulations are not clarified and mentioned in any critical essay. Therefore, in this essay it is tried to criticize these verses according to the external and contextual points. Also some grammatical and rhetorical points as well as common contents of Persian and Arabic literature used in them are shown.